Philosophical and Legal Foundations of the Comprehensive Theory of Law - Zakhartsev, Sergey; Salnikov, Viktor (Տիգրան Մեծ)
The article is devoted to the clarification of the essence of the law. The article examines the ontology of law, and the epistemology of law reflects the philosophical problems of law. The conclusion about the law as a contradictory social phenomenon is formulated. The article substantiates the theory of the comprehensive (all-encompassing) study of law as a philosophical and philosophical-legal theory, the purpose of which is characterized not in the justification of any one theory of law but in the comprehensive study of law, taking into account all available theories. The comprehensive theory allows us to look at the law philosophically, stating the different properties of the object, their manifestations and contradictions. The article argues that it is the philosophical attitude to the law that many scientists lack.
Keywords: Philosophy of law